2011
DOI: 10.1088/0953-8984/23/35/356001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of electronic phase arrest and glassy ferromagnetic behaviour in (Nd0.4Gd0.3)Sr0.3MnO3manganite: comparative study between bulk and nanometric samples

Abstract: The effect of doping of rare earth Gd 3+

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The corresponding ∆R/R 0 and R 0 /R H values at 123 K are 94% and 16.5, respectively. These respective values are comparable to the best-known CMR effects reported for bulk manganite polycrystalline pellets and exceed the parent RE 1-x A x MnO 3 (A = Sr or Ca) around and >100 K. [2,[41][42][43][44][45][46] Table 1 compares the MR values of different parent variants of bulk polycrystalline RE 1-x Sr x MnO 3 with that obtained for the HE-Mn.…”
Section: Correlated Magneto-electronic Properties and Colossalsupporting
confidence: 78%
“…The corresponding ∆R/R 0 and R 0 /R H values at 123 K are 94% and 16.5, respectively. These respective values are comparable to the best-known CMR effects reported for bulk manganite polycrystalline pellets and exceed the parent RE 1-x A x MnO 3 (A = Sr or Ca) around and >100 K. [2,[41][42][43][44][45][46] Table 1 compares the MR values of different parent variants of bulk polycrystalline RE 1-x Sr x MnO 3 with that obtained for the HE-Mn.…”
Section: Correlated Magneto-electronic Properties and Colossalsupporting
confidence: 78%
“…At the grain surface, due to the presence of large number of cluster formation, the long range FM order is disturbed and uncompensated spins start to account for large irreversibility. 12 Increase of the net moment of the grains due to the destabilization of the long range FM order at the surface in these systems is strongly dominated by inhomogeneous clusters. Therefore, the decrease in grain size also gives rise to T B below which the thermal energy cannot overcome the magnetic anisotropy.…”
Section: Resultsmentioning
confidence: 93%
“…That is usually accompanied by a FM-PM transition at the Curie temperature T C . It was shown by many authors that physical properties of Nd 1-x Sr x MnO 3 can be considerably affected by the substitution of the Ln-site by various other elements such as Eu [19], La [20], Pr, Dy [21], Gd [22]. Recently, by doping Y ions into Nd 0.7 Sr 0.3 MnO 3 , Khiem et al [23] have found a decrease of T C and a transition from a metallic phase to an insulating phase when the Y content increased.…”
Section: Introductionmentioning
confidence: 99%